2017
DOI: 10.1177/0192623317737254
|View full text |Cite
|
Sign up to set email alerts
|

Analytical High-resolution Electron Microscopy Reveals Organ-specific Nanoceria Bioprocessing

Abstract: This is the first utilization of advanced analytical electron microscopy methods, including high-resolution transmission electron microscopy, high-angle annular dark field scanning transmission electron microscopy, electron energy loss spectroscopy, and energy-dispersive X-ray spectroscopy mapping to characterize the organ-specific bioprocessing of a relatively inert nanomaterial (nanoceria). Liver and spleen samples from rats given a single intravenous infusion of nanoceria were obtained after prolonged (90 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 58 publications
3
33
1
Order By: Relevance
“…15 One possible explanation might be the dissolution of nanoceria in the liver and subsequent release of cerium ion, resulting in increased cerium in the blood and redistribution to the spleen. 71,84 On the other hand, the observed biokinetic pattern is not consistent with that reported for cerium ion. 14 If this peculiar increase is indeed a true biokinetic phenomenon, better understanding of the underlying physical or physiological mechanisms is needed in order to further develop the PBPK model.…”
Section: Figurecontrasting
confidence: 90%
“…15 One possible explanation might be the dissolution of nanoceria in the liver and subsequent release of cerium ion, resulting in increased cerium in the blood and redistribution to the spleen. 71,84 On the other hand, the observed biokinetic pattern is not consistent with that reported for cerium ion. 14 If this peculiar increase is indeed a true biokinetic phenomenon, better understanding of the underlying physical or physiological mechanisms is needed in order to further develop the PBPK model.…”
Section: Figurecontrasting
confidence: 90%
“…No Ostwald ripening effects were observed in this study where original nanoceria crystals grow due to surface attachment of dissolved ions that come from dissolving nanoceria in the cassette. However, the shedding of ions from nanoceria that are concentrated in macrophages in vivo may provide such supersaturation conditions and this would explain why we observed a dissolution of nanoceria that is accompanied by regrowth of nanoceria or reprecipitation of other cerium phases (cerium phosphate) (Graham et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…HRTEM revealed that the type and degree (intensity) of superstructure formation is ligand-dependent. This may be related to the unique agglomerate assemblies of nanoceria discovered previously in different organs after its intravenous administration, such as in the liver vs. the spleen where nanoceria undergoes organ-specific bioprocessing (Graham et al, 2018). Organ-specific bioprocessing and assemblies of nanoceria may depend on available ligand types and concentrations that modify surface functional properties of the nanoceria after uptake, such as particle charge and ability to complex with available organ-specific molecules.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations